Ejercicio del derecho al trabajo de la población refugiada colombiana en el Distrito Metropolitano de Quito - Cobos Garrido, Vannessa Lucía (2018)
The present investigation analyzed the exercise of the right to work of the Colombian refugee population in the Metropolitan District of Quito, during the period 2008-2017, taking into account that Ecuador is the place to a large number of refugee population, the majority of whom are of Colombian nationality and whose largest percentage is housed in the city of Quito. Considering that the analysis focuses on knowing the situation of this population group when it comes to exercising the right to work, a contrast is made between current regulations at both the national and local levels, as well as the different international instruments subscribed and ratified by our country in terms of refuge with the day to day lives of Colombian refugees in the capital. In order to have a broader view, a survey and the development of interviews with experts were used, as well as the gathering of testimonies from those involved, concluding that the main obstacles for the Colombian population to have access to employment is discrimination, rooted in their nationality, as well as the lack of institutionalization of public policies that provide durable solutions to the issue of refuge.